The Implementation of The Restorative Justice System in the New Indonesian Criminal Law - Imanuddin, Iman; Darusman, Yoyon Mulyana; Yanto, Oksidelfa (Yayasan Sinergi Kawula Muda, 2025)
The regulations of Indonesian criminal law are inherited from Dutch colonial legislation that was incorporated into the Indonesian national legal framework through Article 2 of the transitional provisions of the 1945 Constitution, than officially was established in Law no. 1 of 1945 pertaining to Criminal Law after the independence proclamation. When it was established, the Indonesian penal system was a criminal law intended to offer a punishment and generate a deterrent effect on offenders of criminal activities. As time progresses, with swift societal changes and advancements in information technology, there is a public inclination towards adopting a criminal law system focused on retribution and creating a deterrent effect on offenders that could contemplate utilizing a diversion or restorative justice model. This study employs a socio-legal method utilizing secondary data by analyzing all laws and regulations pertinent to the research. The findings of this study indicate that the government, in reference to Law No. 1 of 2023 on New Criminal Law, has aimed to align with community expectations by releasing policies in the form of regulations from multiple law enforcement bodies to facilitate diversion or restorative justice.